Lack of effect of warfarin on the restenosis rate or on clinical outcome after balloon coronary angioplasty. Issue 6 (December 1988) - Urban, P; Buller, N; Fox, K; Shapiro, L; Bayliss, J; Rickards, A
Abstract : Between September 1985 and April 1987, 110 consecutive patients who had successful coronary angioplasty were included in a randomised prospective controlled evaluation of the effects of warfarin on restenosis. The warfarin (n = 56) and the control (n = 54) groups were not different in terms of age, sex, previous coronary bypass surgery or coronary balloon angioplasty, severity of symptoms, and frequency of multivessel disease or of total coronary occlusions. Warfarin was started on the day of the procedure and the dosage was adjusted to maintain the thromboplastin international normalised ratio greater than or equal to 2.5. One hundred and five (96%) of the patients were given verapamil and other antianginal drugs were prescribed as needed. Low molecular weight dextran and heparin were given during the procedure and heparin was continued for 24 hours in all patients. One hundred and eight (98%) of patients were followed up clinically after a median of five months (range 1-20). Eighty five (77%) had follow up angiography at five months. In the warfarin group symptoms improved in 46 (85%) patients by at least 1 angina class and 31 (57%) were symptom free; the exercise test remained positive in 20 (36%) patients and the angiographic restenosis rate was 25% per lesion and 29% per patient. There were no major bleeding complications. In the control group 46 (85%) patients were improved by at least 1 angina class and 31 (57%) were symptom free; the exercise test was positive in 11 (21%) patients and the angiographic restenosis rate was 33% per lesion and 37% per patient. Although the incidence of angiographic restenosis tended to be lower with warfarin, none of these differences was significant. These data suggest that the combination of verapamil and warfarin, in the absence of aspirin, is not significantly better than verapamil alone in preventing symptom recurrence or angiographic restenosis after coronary angioplasty.